A landscape menu to please them all: Relating users’ preferences to land cover classes in the Mediterranean region of Alentejo, Southern Portugal - Surová, D. (2016)
To address multifunctional land-use management, and as a response to societal expectations with regard to agriculture and well-being in rural spaces, one of the aspects in need of particular attention in the current research is the spatial expression of the landscape attractiveness. Current knowledge about the attributes of landscape that are most highly appreciated, and the ways that individual differences may influence landscape preferences, is still incomplete, particularly for complex agricultural landscapes in the Mediterranean. The aim of this paper is to provide an assessment, including quantitative and qualitative approaches, of user-based landscape preferences in the Mediterranean region of Alentejo, Southern Portugal. To allow for the spatial expression of these preferences and the evaluation of the impact of changes to land-use, specific land cover classes have been used as the basis for our survey. The results are aimed at adding to the body of research literature on the diversity of the landscape attributes that are valued by different user groups and at contributing to informed decision-making processes when resolving land-use issues in the region being studied. To attain this objective, a photo-questionnaire was conducted to identify preferred land cover classes and the land cover qualities that landscape users appreciate most. The study shows that the way that landscape is used is a significant factor influencing the preferences, following a clear functional demand pattern. Not only are there differences between land managers as producers and others as consumers, but the appreciated land cover qualities and land cover preferences also differ from one consumer group to another. Knowledge regarding the preferences of specific groups can inform landscape management at different levels of governance in such a way that multi-functionality may be more successfully attained. Moreover, certain particularities with regard to the preferred landscapes in the region being studied are discussed in comparison with the results of earlier studies from other regions. In this regard, this paper puts great weight on the importance of territorial contextualization in regard to making general assessments concerning landscape preferences.